JOINT OPINION BY THE EXPERT GROUP ON THE ASSESSMENT OF A STUDY FIELD STUDY FIELD (Architecture and Construction) Riga Technical University - Markou, George; Romele, Rinda; Groskaufmanis, Matīss; Liepiņš, Sandris; Todorova, Marija Malenkovska; Richardson, Mark; Lāce, Agnese; Seržants, Rinalds (My University, 2023)
The guidelines for the preparation of the joint opinion (report) by the expert group on the assessment of a study field (hereinafter - the guidelines) have been developed in accordance with Cabinet Regulation No. 793 of 11 December 2018 “Regulations on Opening and Accreditation of a Study Field”. The purpose of the guidelines is to provide the experts with a structured framework for the preparation of the joint opinion on the assessment of a study field. Within the assessment of the study field, the experts shall prepare a joint opinion in English.